An examination of the effect that commitment to a hypothesis has on auditors' evaluations of confirming and disconfirming evidence* - CHURCH, BRYAN K. (Contemporary Accounting Research, 1991)
Research findings by Ashton and Ashton (1988, 1990) and Tubbs et al. (1990) suggest that auditors will readily revise their beliefs in response to new evidence and that they are particularly sensitive to disconfirming evidence. In sharp contrast, research findings in behavioral decision making suggest just the opposite. The prior studies in auditing, however, have not investigated situations in which auditors are likely to become committed to their hypotheses. Auditors who are strongly committed to their hypotheses may be motivated to evaluate mixed (confirming and disconfirming) evidence as being consistent with their hypotheses. The results of a laboratory experiment indicate that level of commitment affected auditors' overall evaluations of mixed evidence. Auditors who were strongly committed to their hypotheses attached more importance to confirming evidence than did auditors who were not strongly committed. Neither group, however, attached significantly different degrees of importance to disconfirming evidence. Résumé. Selon les résultats des travaux d'Ashton et Ashton (1988, 1990) et de Tubbs et al. (1990), les vérificacteurs révisent facilement leur position en réponse aux faits nouveaux et sont particulièrement sensibles aux faits qui viennent infirmer leurs convictions. Ces résultats contrastent beaucoup avec ceux des recherches en comportement décisionnel qui sont parfaitement contraires. Les études précédentes en vérification n'ont cependant pas porté sur les cas dans lesquels les vérificateurs sont susceptibles d'étre liés par leurs hypothèses. Les vérificateurs qui sont fortement liés par leurs hypothèses risquent d'avoir tendance à interpréter les fait mixtes (c'est‐à‐dire les faits qui confirment et infirment leurs convictions) comme étant conformes à leurs hypothèses. Les résultats d'une expérience en laboratoire ont révélé que l'intensité du lien avait une incidence sur l'interprétation globale de faits mixtes par les vérificateurs. Ceux qui étaient fortement liés par leurs hypothèses attachaient davantage d'importance aux faits qui confirmaient leurs hypothèses que ceux qui n'étaient pas fortement liés. Aucun des deux groupes n'attachait une importance très différente aux faits qui infirmaient ses hypothèses.